Dynamics and outcomes of binary collisions of equi-diameter picolitre droplets with identical viscosities. Issue 35 (30th August 2022) - McCarthy, Lauren P.; Knapp, Peter; Walker, Jim S.; Archer, Justice; Miles, Rachael E. H.; Stettler, Marc E. J.; Reid, Jonathan P.
Abstract : Stroboscopic imaging was used to observe the outcomes of binary collisions of picolitre pure water and 40% w/w aqueous sucrose droplets. Abstract : The dynamics of binary collisions of equi-diameter picolitre droplets with identical viscosities, varying impact speeds and impact angles have been investigated experimentally and compared to collision outcome prediction models. Collisions between pairs of pure water droplets with a viscosity of 0.89 mPa s and pairs of aqueous-sucrose (40% w/w) droplets with a viscosity of 5.17 mPa s were examined. The colliding droplets were ∼38 μm in diameter, which is around ten times smaller than those previously investigated when examining the effect of viscosity on the outcome of binary droplet collisions. Varying the impact speed and angle resulted in different collision outcomes, including coalescence, reflexive separation and stretching separation. The collision outcomes were plotted on two viscosity dependent regime maps. The regime boundaries are generally in agreement with earlier literature for both high and low viscosity cases. The agreement between experiment and theory, for both fluids, gives more confidence in the models tested here to predict collision outcomes for droplets of this size and these viscosities.